Nefarious aspects of the Covid-19 pandemic on education policy in Brazil (Research, Society and Development, 2021)
This article addresses the issue of Brazilian education and the effects caused by the Covid-19 pandemic, mainly regarding the acceleration of the precarious process of social policies through the establishment of remote education. A brief discussion is made about elements that make up the dismantling of education in Brazil, such as recklessness, privatization, and distance learning. In order to accomplish this, a bibliographic research was carried out through books, articles and documents on the subject with the objective of supporting the discussion. The investigation shows that the world health crisis brought about a deepening of social inequality and, in relation to education, showed the educational exclusion of people belonging to the working class. In addition, the analysis indicates that the social context then installed strengthens the hegemonic capitalist project.